2023
DOI: 10.3389/fphar.2023.1118216
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of antiseizure drugs on background oscillations in Scn1aA1783V Dravet syndrome mouse model

Abstract: Dravet syndrome (Dravet) is a rare and severe form of developmental epileptic encephalopathy. Antiseizure medications (ASMs) for Dravet patients include valproic acid (VA) or clobazam (CLB), with or without stiripentol (STP), while sodium channel blockers like carbamazepine (CBZ) or lamotrigine (LTG) are contraindicated. In addition to their effect on epileptic phenotypes, ASMs were shown to modify the properties of background neuronal activity. Nevertheless, little is known about these background properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In the CMOS-MEA measurements conducted after CBZ administration, the outcomes revealed an augmentation in activities beyond oscillatory behaviors [Figure 2(Bb)]. Notably, in the ECoG of the DS mouse model, an escalation in spike activities outside of seizure events following CBZ administration has been documented [58]. The response witnessed in our study may potentially mirror the response observed in mouse models, implying a degree of coherence between the findings in our study and the responses seen in the mouse model.…”
Section: Discussionmentioning
confidence: 95%
“…In the CMOS-MEA measurements conducted after CBZ administration, the outcomes revealed an augmentation in activities beyond oscillatory behaviors [Figure 2(Bb)]. Notably, in the ECoG of the DS mouse model, an escalation in spike activities outside of seizure events following CBZ administration has been documented [58]. The response witnessed in our study may potentially mirror the response observed in mouse models, implying a degree of coherence between the findings in our study and the responses seen in the mouse model.…”
Section: Discussionmentioning
confidence: 95%
“…In the mice model of DS, the decreased excitability of fast-spiking interneuron (Yu et al, 2006;Ogiwara et al, 2007) and reduced frequency of spontaneous inhibitory post-synaptic currents in pyramidal neurons (Han et al, 2012;Beretta et al, 2022)has been illustrated as a pathophysiology of DS. This insight is supported by clinical and experimental knowledge that epileptic features can be aggravated by anti-seizure drugs which blocks sodium channel blockers (Wirrell et al, 2022;Quinn et al, 2023). The precise mechanisms underlying the symptoms of DS might be more complex because recent studies provide the evidence that the electrophysiological properties of DS models can be altered depending on age or stage of symptomatic severity (Favero et al, 2018;Almog et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…Because the impairment of fast spiking interneuron firing is regarded as one of the pathophysiological mechanisms of DS, an augmentation of GABA A receptor-mediated inhibition would be the potential therapeutic strategies. Clobazam, one of the benzodiazepine class medications, is often used to treat epilepsy in patients with DS ( Wirrell et al, 2022 ), and its efficacy has been shown in DS model mice ( Hawkins et al, 2017 ; Quinn et al, 2023 ). GABA A receptors are assembled from multiple subunit gene products and form mostly hetero-oligomeric pentamers ( Olsen and Sieghart, 2008 ).…”
Section: Introductionmentioning
confidence: 99%